Dynamically switchable triple-band absorption enhancement of graphene by a subwavelength grating coupled hybrid structure - Shashi Zhang; Haixia Liu; Juan Zhang; Wenjie Li; Hui Wang; Chengxiang Tian; Ling Luo; Lijun Zhao (Results in Physics, 2022)
The dynamically switchable triple-band absorption enhancement over 96% of monolayer graphene in the visible to the near-infrared range is achieved by a simple configuration consisting of subwavelength grating and periodically distributed Bragg reflectors. The isolated optical field distribution enabled by the optical Tamm state (OTS), guided mode resonance (GMR) and Fabry–Perot (FP) mode allows each graphene layer to selectively absorb the incident light in different wavelengths at different parts of the structure, creating favorable conditions for the independent extraction of multi-channel signals. Moreover, the continuous regulation of the absorption wavelength is futher realized by varying the geometrical parameters and dielectric permittivity. Also, the electrical tunability of graphene allows the independent step modulation of the absorption efficiency of three eigenmodes, resulting in the real-time dynamic switching of the system's triple-band/dual-band/single-band operation modes. The proposed structure can be integrated as a dynamic component into other graphene-based multifunctional and switchable optoelectronic devices.